ตอบ:
# f '(x) = (x (LN (x ^ 2 + 3)) ^ (- 1/2)) / (x ^ 2 + 3) = x / ((x ^ 2 + 3) (LN (x ^ 2 + 3)) ^ (1/2)) = x / ((x ^ 2 + 3) sqrt (LN (x ^ 2 + 3))) #
คำอธิบาย:
เราได้รับ:
# การ y = (LN (x ^ 2 + 3)) ^ (1/2) #
# Y '= 1/2 * (LN (x ^ 2 + 3)) ^ (1 / 2-1) * d / DX LN (x ^ 2 + 3) #
# y '= (LN (x ^ 2 + 3)) ^ (- 1/2) / 2 * d / DX LN (x ^ 2 + 3) #
# d / DX LN (x ^ 2 + 3) = (D / DX x ^ 2 + 3) / (x ^ 2 + 3) #
# d / DX x ^ 2 + 3 = 2x #
# y '= (LN (x ^ 2 + 3)) ^ (- 1/2) / 2 * (2x) / (x ^ 2 + 3) = (x (LN (x ^ 2 + 3)) ^ (-1/2)) / (x ^ 2 + 3) = x / ((x ^ 2 + 3) (LN (x ^ 2 + 3)) ^ (1/2)) = x / ((x ^ 2 3) sqrt (LN (x ^ 2 + 3))) #